Yaşlı Dostu Kentler ve Topluluklara İlişkin Kuramsal Çerçevelerin Gözden Geçirilmesi - Ertuğrul Murat Özgür; Neriman Kılınç (Coğrafi Bilimler Dergisi, 2022)
Population ageing and urbanization are two global demographic mega-trends which together shape the 21st century. In this context, within the framework of urban ageing, the initiative called Age-Friendly Cities and Communities (AFFC) is increasingly becoming an important field of interest steering policies aiming to enhance quality of life in old age. This article aims to contribute to national ageing literature by introducing new conceptualization efforts developed rapidly in recent years in the related area and added to the World Health Organization initiative. Through this, drawing more attention of local governments and related stakeholders in charge of planning cities and providing urban services to their residents and providing a conceptual support to the local empirical research of social scientists studying on ageing are thought to be possible. With this understanding, the models developed so far to conceptualize AFFC initiative are revised in this article.